Neutrophil-to-lymphocyte ratio predicts response to cardiac resynchronization therapy - Agacdiken, Aysen (International Scientific Literature, Inc., 2013)
BACKGROUND: Neutrophil-to-lymphocyte (N/L) ratio has been associated with adverse outcomes in patients with acute coronary syndromes and increased risk for long-term mortality in patients with acute decompensated heart failure. We aimed to investigate the prognostic value of neutrophil-to-lymphocyte ratio on response to cardiac resynchronization therapy (CRT). MATERIAL/METHODS: Seventy consecutive patients (mean age 58±13 years; 40 men) undergoing CRT were included in the study. Hematological and echocardiographic parameters were measured before and 6 months after CRT. Echocardiographic response to CRT was defined as a ≥15% reduction in left ventricular end-systolic volume at 6-month follow-up. RESULTS: After 6 months of CRT, 49 (70%) patients were responders. After 6 months, left ventricular ejection fraction (LVEF) had significantly increased, from 21±7% to 34±11% in responder patients (p=0.001). N/L ratio decreased significantly, from 2.4±1 to 2.1±0.7 in responders (p=0.04). In multivariate analysis, significant associates of echocardiographic response to CRT was evaluated adjusting for age, etiology of cardiomyopathy, baseline LVEF, New York Heart Association functional class, C-reactive protein, and baseline N/L ratio. Baseline N/L ratio was the only predictor of response to CRT (OR 1.506, 95% CI, 1.011–2.243, p=0.035). CONCLUSIONS: N/L ratio at baseline could help to identify patients with response to CRT.